Incidents related to the Hickman® catheter: identification of damages - Letícia Pontes; Sandra Regina da Silva; Ana Paula Lima; Lara Cassia Silva Sandri; Ana Paula Batistela; Mitzy Tannia Reichembach Danski
ABSTRACT Objective: to identify damages resulting from incidents with the Hickman® catheter. Method: descriptive, retrospective, qualitative approach. The source of data were the notifications of incidents that occurred between January 2012 and May 2015, as well as the information available on the medical records of patients involved in incidents with the Hickman® catheter. Results: the incidents related to the Hickman® catheter with the greatest impact on patient care were obstruction, fracture and traction. All incidents caused damage to patients, in a greater or lesser degree, in the dimensions of physical damage and subjective damage. Final considerations: damage or potential risk of damage was present in all incidents analyzed. The need to revise cleaning and obstruction protocols for the maintenance of the permeability of Hickman® catheters was demonstrated.